Existence Forms of Economic Systems - Lydeka, Zigmas (Ekonomika, 1999)
The article describes the concept of economics as a continouos people existence form. Thus, the economic motion is widened to the concept of economic existence. In this article the existence of economic system is understood as states of systematic motion that is defined in time and space. The existence means appearance, change and improvement of an economic system. Universal existence forms of an economic system are as follows: 1) self development; 2) external development; 3) transformation. Further in the article the author describes each existence form separately, using graphic illustrations. There are also disccused the criteria according to which it is possible to distinguish among different existence forms. The most important criteria are: qualitative system indications; origin of a system; quantitative and qualitative changes. At the end of the article the author aims to relate existence forms with the economic growth.